Predação e estruturação de habitat por macrófitas modificam a diversidade taxonômica e funcional do zooplâncton. - Deosti, Sabrina (2020)
In Neotropical rivers the predation by fish and the structuring of the habitat by macrophytes influence the dynamics of the zooplankton community, altering the richness and composition of species and the richness and functional composition of the zooplankton and thus the functioning of the ecosystem. We analyzed the influence of macrophytes bank structure and predation by forage fish species on taxonomic and functional zooplankton diversity, estimated by different diversity indices (taxonomic and functional richness, taxonomic beta diversity and functional beta diversity). Thus, we assume that different levels of macrophytes structure and fish predation will alter the taxonomic and functional composition of the zooplankton (alpha and beta) between the analyzed points. Beta diversity was split into two distinct components, turnover and nesting. The zooplankton species richness was positively associated with the macrophytes richness and the macrophytes diversity. In turn, the functional richness of zooplankton had a positive association with fish richness and macrophytes richness. For the variation of total taxonomic beta diversity of zooplankton, the Generalized Dissimilarity Modeling (GDM) explained 32.58% of the total among the predictor variables. The macrophytes biomass represented the taxonomic turnover. The variation in total functional beta diversity of the zooplankton explained 9.98% by the GDM model. The abundance of fish represented the functional nesting. Macrophytes structure represented the taxonomic components and predation represented the functional components. The limnological heterogeneity of the coastal region of the Bay River made possible the colonization by multispecies macrophytes banks, influencing the alteration of the fish and zooplankton community and the more heterogeneous the environmental conditions, the greater is the capacity of colonization of different species, which can present different functional traits. The results indicate the importance of maintaining heterogeneous locations, the need to preserve the tributaries in river floodplain systems as they serve as nursery for fish spawning and contribute to a greater richness of fish, which causes an increase in the functional diversity of zooplankton.